Copper‐Catalyzed Reductive N‐Alkylation of Amides with N‐Tosylhydrazones Derived from Ketones. Issue 14 (27th June 2016) - Xu, Peng; Qi, Fu‐Ling; Han, Fu‐She; Wang, Yan‐Hua
Abstract: A CuI‐catalyzed reductive coupling of ketone‐derived N ‐tosylhydrazones with amides is presented. Under the optimized conditions, an array of N ‐tosylhydrazones derived from aryl–alkyl and diaryl ketones could couple effectively with a wide variety of (hetero)aryl as well as aliphatic amides to afford the N ‐alkylated amides in high yields. The method represents the very few examples for reliably accessing secondary and tertiary amides through a reductive N ‐alkylation protocol. Abstract : A CuI‐catalyzed reductive coupling of ketone‐derived N ‐tosylhydrazones with amides has been developed (see scheme). Under the optimized conditions, an array of N ‐tosylhydrazones derived from aryl–alkyl and diaryl ketones could couple effectively with a wide variety of (hetero)aryl as well as aliphatic amides to afford the N ‐alkylated amides in high yields. The method represents the very few examples for reliably accessing secondary and tertiary amides through a reductive N ‐alkylation protocol.